Near-surface ventilation as a key for modeling the thermal regime of coarse blocky rock glaciers - Pruessner, Luisa; id_orcid:0 000-0001-8125-2426; Phillips, Marcia; Farinotti, Daniel; id_orcid:0 000-0003-3417-4570; Hoelzle, Martin; Lehning, Michael (Permafrost and Periglacial Processes, 2018)
ISSN:1045-6740 ISSN:1099-1530